(untitled) (Revista Iberoamericana de Bioética, 2020)
The use of animals in biomedical research is recognized around the world for its importance to understanding various affectations in the biology and functionality of animal species and particularly the human being. Animals have facilitated the obtaining of knowledge for the prevention, diagnosis and treatment of diverse pathologies involving the physiology and homeostasis of the endocrinal, nervous and immune systems, to mention just part of the complex biology of the human being. So, in the use of animal species through research for the purposes of improving human health, national and international committees have been formed that regulate the handling of live organisms to establish appropriate measures for the selection, handling and use to prevent damage to the individuals in the research process. However, the involvement of non-human animals does not always take place in the best conditions for the individual animals used for clinical and biomedical purposes. This makes it necessary to obtain information about research with non-human animals considering their involvement and the development conditions of the species involved, along with the protocols and regulations governing this scientific practice. It is also important to ascertain the trends in bioethical responsibility in many countries for lines of research like biomedicine and medicine in relation to the use of many animal species in humans for health purposes.